Analisis Real sebagai Dasar Matematika untuk Pengembangan Kecerdasan Buatan dan Machine Learning - Ghina Putri Andini; Maryani; Depriwana Rahmi; Suci Yunianti; Annisa Kurniati (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the role of fundamental concepts of Real Analysis as a mathematical foundation in the development of artificial intelligence and machine learning through a literature review. Concepts such as limits, continuity, and convergence are directly related to the optimization process used in model training, making a deep theoretical understanding essential in modern computing (Goodfellow et al., 2016). Data were obtained from various theoretical books, national and international journal articles, and applied mathematics research, then analyzed using content analysis techniques to explore patterns and contributions of the literature. The results of the study confirm that Real Analysis not only serves as a theoretical foundation of mathematics but also plays a strategic role in ensuring the stability and accuracy of artificial intelligence algorithms, making mastery of these concepts a crucial requirement in supporting technological development and improving the quality of mathematics learning.